Impact of Green Banking Practices on Sustainable Banking: A Case of Commercial Banks in Pakistan (Journal of Asian Development Studies, 2023)
The global focus on environmental protection and corporate social responsibility has brought significant attention to sustainable banking in recent years. Green banking practices aim to incorporate environmental considerations into the operations and decision-making processes of the financial sector. Despite the increasing awareness and significance of sustainable banking practices, the adoption and implementation of green banking initiatives in Pakistan's banking sector remain limited. The study examined the impact of green banking practices on sustainable banking in Pakistan. The participants of the study included 320 banking sector employees working at public sector banks in Pakistan. The study was cross-sectional in nature and data were collected from the respondents using a survey questionnaire administered by the principal author. Questionnaires measured five green banking practices (perceived usefulness=6 items, perceived ease of use=4 items, management control and support=5 items, competitor pressure=5 items, customer pressure=5 items) and sustainable banking (7 items). Using SPSS Version 27, the results of linear regression analysis revealed that perceived usefulness brings 13% change, perceived ease of use brings 18% change, management control and support brings 25% change, competitor pressure brings 21% change and customer pressure brings 29% change in sustainable banking. This study offers insight into understanding the proposed relationships in the novel context of the banking sector of Pakistan. Based on the findings of the study, we have discussed the implications of the study and offered directions for further research.